Optical properties of intracloud and cloud-to-ground discharges derived from JEM-GLIMS lightning observations. (August 2019) - Bandholnopparat, K.; Sato, M.; Adachi, T.; Ushio, T.; Takahashi, Y.
Abstract: We developed a new method to distinguish the lightning discharge type using lightning data obtained by JEM-GLIMS spaced-based mission and ground-based lightning network that are JLDN, NLDN, WWLLN, and GEON. As a first step, we selected 1057 lightning events detected by the JEM-GLIMS cameras (LSI) and spectrophotometers (PH) in 2014. Then, we compared the JEM-GLIMS optical data to the ground-based lightning data in order to check the simultaneous detection of JEM-GLIMS lightning events by the ground-based lightning networks, and finally we identified the discharge type of the JEM-GLIMS lightning events. We succeed in identifying 941 simultaneous lightning events and found that 582, 93, and 266 lightning events were IC, +CG, and -CG discharges, respectively. As a next step, we calculated intensity ratios between blue and red PH channels, i.e., 337nm/762 nm, 316nm/762 nm, 392nm/762 nm, 337nm/(599–900 nm), 316nm/(599–900 nm), and 392nm/(599–900 nm) for the 941 lightning events in order to specify the optical characteristics of IC, +CG, and -CG discharges. It is found that the PH intensity ratio of +CG discharges is the highest and that the PH intensity ratio of IC and -CG discharges is smaller than that of +CG discharge. We also found that the characteristics of the LSI intensity ratio are almost comparable to those of the PH intensity ratio. As the differences of the 337nm/762 nm, 337nm/(599–900 nm), and 392nm/(599–900 nm) ratio of IC, +CG, and -CG discharges are relatively large, these three ratios are a useful proxy for classifying the discharge types for additional 7349 lightning events detected by JEM-GLIMS in order to estimate the global ratio between IC and CG discharges ( Z ratio). Highlights: Method to distinguish the lightning discharge type using JEM-GLIMS optical data is newly developed. The PH intensity ratio and the LSI intensity ratio of IC discharges are different from those of +CG and -CG discharges. The PH2/PH3, PH2/PH4 and PH6/PH4 ratio are the useful proxy to distinguish the discharge types.